1977
DOI: 10.1103/physrevb.15.926
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect two-photon processes in layered semiconductors

Abstract: Two-photon absorption measurements have been carried out in the layered compounds GaSe, PbI2, and GaS using single-wavelength excitation by a neodymium and a ruby laser. The absorption coefficient for direct interband transitions has been measured in all materials by the nonlinear transmittance method. Nonlinear photoconductivity measurements allowed the determination of a nonlinear absorption coefficient for indirect transitions in GaS and the determination of free-carrier lifetime in all three materials. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

1984
1984
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(13 citation statements)
references
References 17 publications
0
11
0
2
Order By: Relevance
“…: 20 15 Laser intensity exceeds the upper limit given by (28) only in order to 1 illustrate the asymptotical behavior ofthe rates for large laser intensities. 11 12 13 14 15 1og101, (W/cm2) Then the exponential factor in (20) becomes exactly the same as in expression (16) in Keldysh's paper1 while the slow amplitude differs from that for the atomic case given by (1 8) in Ref. 1 .…”
Section: ) 4ma2)mentioning
confidence: 80%
See 1 more Smart Citation
“…: 20 15 Laser intensity exceeds the upper limit given by (28) only in order to 1 illustrate the asymptotical behavior ofthe rates for large laser intensities. 11 12 13 14 15 1og101, (W/cm2) Then the exponential factor in (20) becomes exactly the same as in expression (16) in Keldysh's paper1 while the slow amplitude differs from that for the atomic case given by (1 8) in Ref. 1 .…”
Section: ) 4ma2)mentioning
confidence: 80%
“…3) twice per period of the field oscillations. Then the condition (9) is equivalent to the condition <<1, (11) F that is obvious from Fig. 4 and the discussions above.…”
Section: Electron Motion Under Action Of Time-dependent Electric Fieldmentioning
confidence: 85%
“…Saturable absorption characteristics depend on the properties of a materials and the parameters such as intensity and pulse duration of laser used [16][17][18]. It is well known that when the photon energy h is less than the band gap Eg, 2 PA and 3 PA processes are dominant mechanisms as observed in semiconducting materials [19][20][21]. At low input irradiance, Figures 2 and 4 in case of indirect band gap crystals in our open aperture Z-scan measurements, the 532 nm and 1064 nm laser radiation yielding SA.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental as well as theoretical investigations performed in pure CdI 2 single crystals in the last few years using nonlinear spectroscopy have shown that CdI 2 possesses higher-order optical nonlinearities [ 5 - 8 ]. An investigation for the magnetic field stimulated ferroelectricity in CdI 2 –Cu has also been reported [ 9 ].…”
Section: Introductionmentioning
confidence: 99%